Capability of Catfish (Clarias gariepinus) to Accumulate Hg2+ From Water - Heny Suseno (Graduate Program of Syiah Kuala University, 2015)
Mercury is hazardous contaminant that can be accumulated by aquatic organisms such as fishes, mussels etc. Catfish is one of source of animal protein but it also can accumulate Hg2+ from water that used in aquaculture. Due to less information about capability of catfish to accumulate Hg2+, therefore we studied bioaccumulation of Hg2+ that used biokinetic approach (aqueous uptake-rate, and elimination-rate). Nuclear application technique was applied in this study by using radiotracer of 203Hg. A simple kinetic model was then constructed to predict the bioaccumulation capability of by catfish. The result of experiments were shown that the uptake rate of difference Hg2+ concentration were 79.90 to 101.22 ml.g-1.d-1. Strong correlation between uptake rates with increasing Hg2+concentration. In addition, the elimination rates were range 0.080 – 0.081 day-1. The biology half time (t1/2b) of Hg2+ in whole body catfish were 8.50 – 8.63 days. However, no clear correlation between elimination rate with increasing concentration of Hg2+. The calculation of Bio Concentration Factor (BCF) shown catfish have capability to accumulated Hg maximum 1242.69 time than its concentration in water